Home Intravenous Self-Injection of Antibiotic Therapy - Alain Y Martel (Canadian Journal of Infectious Diseases)
The current medical climate has forced all health care providers to search for alternative methods for the delivery of health care. This search has led to the use of sites outside the conventional hospital walls for peritoneal dialysis, parenteral hyperalimentation, blood or blood product transfusions, etc. Home intravenous self-injection of antibiotics is such an alternative to prolonged and/or repeated hospitalization for patients requiring intravenous antibiotics administration only. This alternative was started as a pilot study and soon became a usual service in the Centre hospitalier de l’Université Laval following receipt of a grant from the National Health Research and Development Program. After careful development of inclusion/exclusion criteria and a teaching manual for patient and health care providers. and the standardization of medical. pharmaceutical and nursing approach, a clinical, psychosocial and economical analysis of patients who agreed to participate in a clinical study comparing the two methods of health care delivery (hospital versus home) was started. Patients who met inclusion/exclusion criteria, agreeing to finish their treatment at home instead of staying hospitalized to receive intravenous antibiotics only, were taught the various techniques of intravenous self-injection. Once they were judged to be able to self-administer the antibiotics, they were sent home with the material needed to carry on their treatment, To date, more than 100 patients have participated in the home-treatment, of which 50 were analyzed. The duration of home treatment varied from two days to several months. Most patients had osteomyelitis, septic arthritis, septic bursitis, bacterial cellulitis or lung infections. The therapy allowed some newly defined patients with complicated infections (AIDS patients with cytomegalovirus retinitis) to continue their treatment at home. The clinical outcome of patients treated at home was identical to the outcomes of those treated in the hospital. Side effects were comparable with the hospital treatment and were mainly catheter-related. Compared with hospitalization. home treatment was preferred by the majority of patients. Psychological analysis of the patients showed that those who choose home therapy had a higher internal “locus of control” than those who preferred to stay in the hospital for the entire length of therapy. The economical analysis showed a potential reduction of cost varying between $941.00 and $3325.00 per treatment. Home intravenous self-injection of antibiotics allowed health self-monitoring by the patients or/and their friends or family and increased health care efficiency.